Traditional Knowledge Progress report: 2017-2019 - Conservation of Arctic Flora and Fauna (CAFF) (Arctic Council Secretariat, 2019)
Progress report 2017-2019. The Arctic Council recognizes the importance of Traditional Knowledge (TK) and there is a growing appreciation for utilizing TK, Local Knowledge and science through a collaborative approach. This progress report provides an overview of efforts to include TK within the work of CAFF and describes progress during the 2017-19 Arctic Council Ministerial period. While progress has been made it is important to note that a lack of funding support and capacity hinders effective utilization of TK and TK holders within CAFF activities.